Male and female behavioral variability and morphine response in C57BL/6J, DBA/2J, and their BXD progeny following chronic stress exposure - Carole Morel; Lyonna F. Parise; Yentl Y. Van der Zee; Orna Issler; Min Cai; Caleb J. Browne; Anthony Blando; Katherine B. LeClair; Antonio V. Aubry; Sherod Haynes; Robert W. Williams; Megan K. Mulligan; et al. (Scientific Reports)
Abstract Drug addiction is a multifactorial syndrome in which genetic predispositions and exposure to environmental stressors constitute major risk factors for the early onset, escalation, and relapse of addictive behaviors. While it is well known that stress plays a key role in drug addiction, the genetic factors that make certain individuals particularly sensitive to stress and, thereby, more vulnerable to becoming addicted are unknown. In an effort to test a complex set of gene x environment interactions—specifically gene x chronic stress—here we leveraged a systems genetics resource: BXD recombinant inbred mice (BXD5, BXD8, BXD14, BXD22, BXD29, and BXD32) and their parental mouse lines, C57BL/6J and DBA/2J. Utilizing the chronic social defeat stress (CSDS) and chronic variable stress (CVS) paradigms, we first showed sexual dimorphism in social and exploratory behaviors between the mouse strains. Further, we observed an interaction between genetic background and vulnerability to prolonged exposure to non-social stressors. Finally, we found that DBA/2J and C57BL/6J mice pre-exposed to stress displayed differences in morphine sensitivity. Our results support the hypothesis that genetic variation influences chronic stress-induced behavioral outcomes such as social and approach-avoidance behaviors, reward responses, as well as morphine sensitivity, and is likely to modulate the development of drug addiction.